PENDAMPINGAN DIGITALISASI SEKOLAH SMPIT AJIMUTU GLOBAL INSANI TAMBUN UTARA-BEKASI MENUJU MANAJEMEN SEKOLAH BERBASIS DIGITAL - Saryoko, Andi; Aziz, Faruq; Elyana, Instianti; Kurniyawantoro, Kurniyawantoro; Saputra, Bagas Eka (LPPM Universitas Nusa Mandiri, 2024)
In the digital era, the application of information technology in schools is crucial to enhance the efficiency and quality of educational management. This Community Service (PkM) activity aims to assist Sekolah Menengah Pertama Islam Terpadu (SMPIT) Ajimutu Global Insani Tambun Utara-Bekasi in implementing digital-based school management. The main objective of this activity is to optimize the school's management system through a tailored application that meets the school's needs, called DigiMS (Digital School Management). DigiMS will be built web-based which will be hosted and use a domain name, and a mobile-based application will be created which will be submitted to the Playstore. The method used includes stages of analyzing the existing school management system, developing the DigiMS application, providing training for staff and teachers on how to use the application, and monitoring and evaluating the application's implementation. Data was collected through direct observations at the partner school, interviews with staff, and efficiency measurements before and after the implementation of the digital system. The results of this activity showed a significant increase in operational efficiency, especially in student data management, financial administration, and internal and external communication. The main conclusion from this program is that adopting digital-based management through DigiMS can improve the effectiveness of school management and ease staff workloads in their daily tasks. Additionally, this program has a positive impact on the school's readiness to face the challenges of the digital era. This program is part of the 2024 Fiscal Year PKM Grant from Kemdikbudristek-DRTPM, conducted by lecturers and students from Universitas Nusa Mandiri.